Acute syndesmotic instability in ankle fractures: A review. Issue 3 (September 2017) - van Zuuren, W.J.; Schepers, T.; Beumer, A.; Sierevelt, I.; van Noort, A.; van den Bekerom, M.P.J.
Highlights: Over a 100 publications relating to the management of syndesmotic injuries of the ankle joint were reviewed. Both diagnosing syndesmotic instability as the treatment of this injury are discussed. Despite the abundance of literature and the wide variety concerning this topic, some recommendations for clinical practice are made. Abstract: Ankle fractures are among the most common fracture types, and 10% of all ankle fractures lead to accessory syndesmotic injury. An injury that is challenging in every respect is syndesmotic instability. Since the range of diagnostic techniques and the therapeutic options is extensive, it still is a controversial subject, despite the abundance of literature. This review aimed to summarize the current knowledge on syndesmotic instability in ankle fractures and to formulate some recommendations for clinical practice. Chronic instability and the operative osseous treatment of ankle fractures are not part of this review.